Inequality in Mortality: Updated Estimates for the United States, Canada and France. (29th April 2021) - Baker, Michael; Currie, Janet; Miloucheva, Boriana; Schwandt, Hannes; Thuilliez, Josselin
Abstract: This study provides comparisons of inequalities in mortality between the United States, Canada and France using the most recent available data. The period between 2010 and 2018 saw increases in mortality and in inequality in mortality for most age and gender groups in the United States. The main exceptions were children under 5 and adults over 65. In contrast, Canada saw a further flattening of mortality gradients in most groups, as well as further declines in overall mortality. The sole exception was Canadian women over 80 years old, who saw small increases in mortality rates. France saw continuing improvements in mortality rates in all groups. Both Canada and France have distributions of mortality that are much more equal than those in the United States, demonstrating the importance of public policy in the achievement of equality in health.